Oocyte-specific disruption of adrenomedullin 2 gene enhances ovarian follicle growth after superovulation - Chang, Chia Lin; Lo, Wei-Che; Lee, Ta-Hsien; Sung, Jia-Yi; Sung, Yen Ju (Frontiers in Endocrinology, 2022)
Background: Adrenomedullin 2 (ADM2), adrenomedullin (ADM), and calcitonin gene-related peptides (α- and β-CGRPs) signal through heterodimeric calcitonin receptor-like receptor/receptor activity-modifying protein 1, 2 and 3 (CLR/RAMP1, 2 and 3) complexes. These peptides are important regulators of neurotransmission, vasotone, cardiovascular development, and metabolic homeostasis. In rodents, ADM is essential for regulating embryo implantation, fetal–placental development, and hemodynamic adaptation during pregnancy. On the other hand, ADM2 was shown to affect vascular lumen enlargement, and cumulus cell-oocyte complex (COC) communication in rodent and bovine ovarian follicles. To investigate whether oocyte-derived ADM2 plays a physiological role in regulating ovarian folliculogenesis, we generated mice with oocyte-specific disruption of the Adm2 gene using a LoxP-flanked Adm2 transgene (Adm2 loxP/loxP) and crossed them with Zp3-Cre mice which carry a zona pellucida 3 (Zp3) promoter-Cre recombinase transgene. Results: While heterozygous Adm2 +/-/Zp3-Cre and homozygous Adm2 -/-/Zp3-Cre mice were fertile, Adm2 disruption in oocytes significantly increased the number of ovulated oocytes following a superovulation treatment. Oocyte-specific Adm2 disruption also significantly impaired the developmental capacity of fertilized eggs and decreased the size of the corpus luteum following superovulation, perhaps due to a reduction of ovarian cyclin D2-associated signaling. Conclusions: The disruption of intrafollicular ADM2 signaling leads to follicular dysfunction. These data suggested that oocyte-derived ADM2 plays a facilitative role in the regulation of hormonal response and follicle growth independent of the closely related ADM and CGRP peptides, albeit in a subtle manner.